The Changing Landscape of International Education Research - Proctor, Douglas (International Higher Education, 2016)
An analysis of how research relating to international higher education is used by researchers and policy makers, this article discusses the impact of journals and articles. A full report presenting analysis of 2011–2013 data from the IDP Database of Research on International Education, and an infographic presenting key 2011–2014 trends, are available on the International Education Research Network web site at www.ieaa.org.au/iern.